Synthesis and characterization of NI-based catalysts modified with rare earth and alkaline metal oxides (CeO2, La2O3, BaO) for methane cracking - Asmida, Ideris
Nickel (Ni) has been recognized as a low-cost and an efficient catalyst for hydrogen production from methane cracking. Nevertheless, methane cracking reaction is still hindered by accumulation of carbon on Ni catalyst, which is produced during the reaction. Modification of Ni catalyst with other substance known as promoter is essential to reduce the carbon deposition. Additionally, supported catalyst with relatively large surface area and highly catalyst dispersion for example is essential to develop carbon-resistance Ni-based catalysts. In order to evaluate the effect of promoter, Ni metal has been modified with cerium (Ce), lanthanum (La) and barium (Ba) and a self-combustion process, glycine- nitrate process (GNP) has been employed for the catalyst preparation method. Effects of glycine-nitrate (G/N) ratio and calcination temperature have been investigated on Ni catalyst properties and morphology. Ni catalyst with modified La supported on an inert support, SiO2 (Ni-La/SiO2) was further chosen for catalytic activity in methane cracking. In situ self-combustion has been employed where the inert SiO2 support is immersed into the fuel-nitrate solution where the solution is allowed to self-ignited. Effects of support sizes, support loading, La loading and reaction gas concentration have been evaluated on catalyst activity and carbon formation. All Ni catalysts modified with Ce, La and Ba are very high in crystallinity. The reduced catalyst of Ni catalyst modified with Ce composed of Ni and CeO2, the reduced Ni modified with La catalyst composed of separated phases of Ni and La2O3 while the reduced Ni catalyst modified with Ba composed of Ni and BaN2O6. The Ni-Ba catalyst however does not contain BaO as expected. In all catalysts, morphology of the catalyst is highly influenced by the G/N ratio. Catalyst with G/N= 0.5 ratio displays a foam-like open-pore structure with non-uniform macropores while G/N= 1.5 produce catalyst with small pores with the presence of denser surfaces. G/N=1.0 ratio is the optimum G/N as it produced catalyst with large and more uniform macropores. Meanwhile 800°C was found to be the best calcination temperature for Ni metal catalysts modified with Ce, La and Ba. From catalytic activity through methane cracking, Ni−La/SiO2 supported with SiO2 support with a lower particle size has a better conversion than the shown by Ni-La/SiO2 with a support of larger particle size. Initial H2 yield for Ni−La/SiO2 supported with SiO2 support with a lower particle size was higher compared that for by Ni-La/SiO2 with a support of larger particle size. Catalyst dispersion calculated for Ni−La/SiO2 supported with SiO2 support with a lower particle size is higher than the one with a support of larger particle size, suggesting that catalyst supported on a support of high surface area has a better catalyst dispersion. Higher support loading also gave better catalyst dispersion. Nevertheless, massive amount of filament carbons is found on the surface of Ni−La/SiO2 supported with SiO2 support with a lower particle size catalyst suggesting that the catalyst is very active for catalytic activity. In Ni/SiO2 without La, high initial methane conversion of 58% was achieved yet the conversion was drop gradually to 30% after 150 minutes of reaction time. As 5% of La was added into Ni catalyst, the methane conversion was maintained at lower ~40% throughout the experiment. Further increase of La to 20% has reduced the methane conversion to ~38%. Reaction gas composition CH₄: N₂= 1:2 have the highest methane conversion initially at ~75% and as the methane concentration decreased, the initial methane conversion decreased. In conclusion, the work has successfully synthesized Ni modified with La catalyst supported on SiO2 (Ni-La/SiO2) using in situ glycine- nitrate process of high dispersion, thus resulted in a decent catalytic activity in methane cracking.